The Influence of Islamic Rhetoric on the Emotions of Tablighi Congregants on Ustadz Adi Hidayat’s Social Media Platforms - N, Nasichah; Nadzwa, Putri; ’Aisy, Bintang Balqis Rihhadatul; Chaerunisa, Zahwa (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islamic rhetoric is the art of speaking that combines linguistic aesthetics, sincerity of heart, and spiritual strength in conveying da'wah messages. In the digital era, Islamic rhetoric is not only practiced from pulpits and in mosques but has also rapidly developed on social media platforms such as YouTube. This study aims to analyze the influence of Islamic rhetoric on congregational emotions in digital sermons delivered by Ustadz Hanan Attaki, Ustadz Ali Hidayat, and Ustadz Abdul Somad. The approach used is descriptive quantitative, employing content analysis techniques to examine communication style, language use, intonation, and expressions utilized by the preachers on YouTube. The results indicate that gentle, communicative, and heart-touching Islamic rhetoric is able to evoke positive emotions such as emotional resonance, enthusiasm, and inner peace among the audience. In addition, emotional interactions in the YouTube comment sections demonstrate engagement between the da‘i (preachers) and the audience. In conclusion, Islamic rhetoric is not merely a means of conveying religious teachings but also a tool of psychological transformation that can strengthen faith and enhance the spiritual awareness of congregants in the digital era.